Gender Role and Time Allocation in Integrated Rice Field Farmer's Household Cattle - Abdul Rizal; Yosehi Mekiuw; Silas Tanggu Redu; Ni Wayan Pradnya; Paramita Paramita; Wa Ode Suriani (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2022)
This study aims to determine gender roles and gender time allocation in rice farming households integrated with cattle. This research was conducted in Semangga Jaya Village, Semangga District, Merauke Regency. Analysis of the data used is a different test. The results of this study indicate that the roles of husbands and women in production, reproduction, and social activities are balanced. Women and men have equal access and roles for the three accesses. For time allocation, women allocate the highest time to household activities while men to activities in farming. Women and men have equal access to every activity, this happens based on an agreement in the household.